Estrategia de aprendizaje en la asignatura de Ciencias Naturales para los estudiantes de Educación Básica Superior modalidad Semipresencial de la Unidad Educativa Comunitaria Intercultural Bilingüe El Chaquiñan. - Gallardo Tirado, Gloria Margoth (2020)
This developed investigation carried out addressed a problem framed in the low performance of students of the UECIB "El Chaquiñan" related to the low level of knowledge of the students about the existence and application of learning strategies, that allow to catch the attention of students to taste for learning and for cultivating the intellectual and cultural aspect of their minds. For the solution, it is proposed to develop a strategy for the learning of Natural Sciences for students of the Higher Basic Education levels in the blended modality. This investigation was developed under a qualitative-quantitative approach, so he used observation and survey to diagnostic the situation of Natural Science learning strategies for UECIB students "El Chaquiñán". Which have allowed to obtain as a result that teachers not have innovative strategies for teaching CCNN, students have not assumed the active role in education, so 68.4% of students sometimes look for their own strategies to learn and perform their tasks and 10.5% never do. Which led to the conclusion that the proposal contributes significantly to improve the learning of CCNN in students, so that a series of activities framed in the developed learning.